Kontribusi musala Olivia sebagai katalisator dalam pencapaian Tujuan Pembangunan Berkelanjutan - Agus Kurnia; Jamaluddin; Dalmeri; Muhamad Aditio Apriesta Suharto; Atma Utami Sawitri; Nurul Fitriyani (ADPISI (Asosiasi Dosen Pendidikan Agama Islam Se-Indonesia), 2024)
Musala Olivia is one of the places of worship and social activities located in Jonggat Village, Central Lombok Regency, West Nusa Tenggara. This study aims to analyze Musala Olivia's contribution to the Sustainable Development Goals (SDGs) which is a global agenda to create a better world. Qualitative methods were used in this study by conducting interviews with the management of Musala Olivia, observations of activities in Musala Olivia, and documentation studies of relevant sources. The results showed that Musala Olivia contributed positively to several aspects of the SDGs, such as quality education, poverty alleviation, hunger alleviation, health and well-being, and partnerships to achieve the goals. Some activities carried out by Musala Olivia, such as children's and adult studies, providing compensation to the poor and orphans, free food and drink services to visitors, and cooperation with various parties, are forms of implementation of Islamic rahmatan lil alamin values. This research provides an illustration for mosque and musala takmir, academics, government, and the community to work together in the role and function of mosques and musala around which can provide direct benefits to the community as well as in supporting the Sustainable Development Goals which are common goals towards a better society.